RELIGIOUS MODERATION CAMPAIGN: ENCOUNTERING PEACE, FOSTERING NATIONALISM, AND IMPROVING SPIRITUALITY TOWARD MADRASAH’S STUDENTS - Fitriyah, Zakiyatul; Anggarini, Ida Fitri; Haramein, Zia Ul; Syatta, M. Miqdad Al Ghifari; Dausar, Zakky Muhammad (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2025)
Any educational level needs to share and practice religious moderation. Additionally, there have been several mishaps in this digital age that call for religious moderation and its ideals such as intolerance, radicalism, extremism, and or degrading spirituality. This study examined the most effective methods used by the religious moderation campaign educators after their initial introduction by MoRA from September 2021 up to now to encounter peace, foster nationalism, and improve students’ spirituality at one Madrasah in Malang Regency.  In-depth interviews and documentation were used in this qualitative study to gather information from the researcher's experiences. The findings indicate that: 1) encountering peace through inserting the values of religious moderation in madrasah. Such as daily activities in the madrasah, discussing current issues, or winning numerous prizes to boost students' motivation, performance, and understanding of the values of religious moderation 2) fostering nationalism faced possibilities and obstacles. 3)Additionally, improving spirituality by creating them as the Moderator Agent. Meanwhile, the digital campaign is essential to spread positive news, encounter peace, stop hoaxes and hate speech, and understand the pressing issues. The findings suggest that this campaign has a favorable influence on educators and students, such as increasing nationalism and tolerance. Setiap jenjang pendidikan perlu berbagi dan mempraktikkan moderasi beragama. Terlebih lagi, di era digital ini telah terjadi berbagai insiden yang menuntut pentingnya moderasi beragama dan nilai-nilainya, seperti intoleransi, radikalisme, ekstremisme, dan penurunan spiritualitas. Penelitian ini mengkaji metode paling efektif yang digunakan oleh para pendidik dalam kampanye moderasi beragama setelah diperkenalkan pertama kali oleh Kementerian Agama sejak September 2021 hingga sekarang, dalam rangka menciptakan kedamaian, menumbuhkan nasionalisme, dan meningkatkan spiritualitas siswa di salah satu madrasah di Kabupaten Malang. Penelitian kualitatif ini menggunakan wawancara mendalam dan dokumentasi untuk mengumpulkan data berdasarkan pengalaman peneliti. Temuan menunjukkan bahwa: 1) menciptakan kedamaian dilakukan melalui penyisipan nilai-nilai moderasi beragama di madrasah, seperti dalam kegiatan harian, diskusi isu-isu terkini, atau perolehan berbagai penghargaan guna meningkatkan motivasi, kinerja, dan pemahaman siswa terhadap nilai-nilai moderasi beragama; 2) upaya menumbuhkan nasionalisme dihadapkan pada berbagai peluang dan tantangan; 3) peningkatan spiritualitas dilakukan dengan menjadikan siswa sebagai Agen Moderator. Sementara itu, kampanye digital sangat penting untuk menyebarkan berita positif, menciptakan kedamaian, menghentikan hoaks dan ujaran kebencian, serta memahami isu-isu aktual. Temuan menunjukkan bahwa kampanye ini memberikan pengaruh positif bagi para pendidik dan siswa, seperti meningkatnya nasionalisme dan toleransi.